2020
DOI: 10.1016/j.ijid.2020.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Presence and diversity of Leishmania RNA virus in an old zoonotic cutaneous leishmaniasis focus, northeastern Iran: haplotype and phylogenetic based approach

Abstract: Objective: Leishmania RNA virus (LRV) is a double-stranded RNA (dsRNA) virus that circulates within many species of the Leishmania parasite. In this study, we aimed to investigate the presence of LRV2 circulating in Leishmania isolates in an old focus of ZCL located in northeastern of Iran. Methods: Leishmania isolates were collected from 85 patients that confirmed to have cutaneous leishmaniasis (CL) based on parasitological examination. To identify the Leishmania isolates, speciesspecific primer sets were ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 27 publications
6
19
0
Order By: Relevance
“…According to previous evidence, studies have been conducted to investigate the presence of Leishmania RNA virus in Iran. It is interesting to know that Leishmania RNA virus has been detected in many L. major species and one L. infantum isolated from a VL patient, and one L. tropica isolated from a CL patient in Iran (110,183).…”
Section: Discussionmentioning
confidence: 99%
“…According to previous evidence, studies have been conducted to investigate the presence of Leishmania RNA virus in Iran. It is interesting to know that Leishmania RNA virus has been detected in many L. major species and one L. infantum isolated from a VL patient, and one L. tropica isolated from a CL patient in Iran (110,183).…”
Section: Discussionmentioning
confidence: 99%
“…LRV2 was detected in L. major [ 21 ], Leishmania infantum [ 22 ], Leishmania aethiopica [ 18 , 49 ], and Leishmania tropica [ 50 ]. Two studies conducted in Iran, in a zoonotic focus of cutaneous leishmaniasis (CL) and including visceral leishmaniasis (VL) patients, reported that the virus was detected in two different parasite specimens: one L .…”
Section: A Brief History Of the Detection And Dispersion Of Lrv1 Lrv2 And Lbvmentioning
confidence: 99%
“…Fifty-nine (69.4%) presented LRV2, and one out of the two L . tropica isolates was also positive for LRV2 [ 50 ]. L .…”
Section: A Brief History Of the Detection And Dispersion Of Lrv1 Lrv2 And Lbvmentioning
confidence: 99%
“…By using these intrinsic LEVs, Leishmania parasites retained sophisticated survival pathways in their most ancient evolution [70][71][72][73][74]. Overall, LEVs are heterogeneous, membrane-limited structures that play important roles in numerous biological processes, both pathophysiological and physiological, and in specific intercellular crosstalk between cells, transferring information through multiple cargoes and modulating the immune system of the host [70][71][72]75,76].…”
Section: Leishmania Extracellular Vesicles (Levs): Do We Know Everything?mentioning
confidence: 99%
“…The LEVs released from the promastigotes and amastigotes is a potentially ample field of research, which provides the background for comparative studies of the LEVs, which identified a positive selection mechanism in the poorly known mutualistic relationship of L. (V.) guyanensis and the LRV1 endovirus [70,72]. Ancient Leishmania lineages infected naturally with an endosymbiotic non-enveloped RNA virus might maximize Leishmania infectivity by subverting the immune response as a determinant of disease severity related to the co-circulation of the Leishmania viruses (LRV1 and LRV2) in the zoonotic focus on leishmaniasis in both the New and Old Worlds [70,[72][73][74]. There is some evidence that parasites infected with the LRV1 virus may be more pathogenic in experimental models and in humans, exacerbating the aggressiveness of muco-cutaneous leishmaniasis [70,72,73].…”
Section: Leishmania Extracellular Vesicles: What We Know So Farmentioning
confidence: 99%